Investigation of the Extraction Parameters on Acquisition of Natural Colorants from Coleus atropurpureus L. Benth Leaves Using Microwave- and Ultrasonic-Assisted Extraction - Yuniati, Yuyun; Gala, Selfina; Sumarno, Sumarno; Mahfud, Mahfud (Indonesian Food Science and Technology Journal, 2025)
Abstract— This study systematically investigates the application of Microwave-Assisted Extraction (MAE) and Ultrasonic-Assisted Extraction (UAE) to extract natural pigments from Coleus atropurpureus L. Benth leaves, using water as a green solvent. These advanced techniques were selected over conventional methods due to their well-documented advantages, including shorter extraction times, higher extraction efficiencies, and reduced environmental impact through lower solvent consumption. Importantly, MAE and UAE are particularly suitable for isolating thermolabile compounds such as plant pigments, as they minimize thermal degradation while enhancing yield. Key extraction parameters (feed-to-solvent ratio (F/S), particle size, extraction time, temperature, microwave power, and ultrasonic frequency) were systematically varied to evaluate their influence on extraction performance. Additionally, an air flow system was integrated into both setups to study the effect of controlled airflow (1 to 4 L/min) on pigment yield. For MAE, optimal conditions included 400 W microwave power, an F/S ratio of 0.01 g/mL, particle size greater than 40 mesh, 40 minutes extraction time, and an airflow rate of 1 L/min. In the case of UAE, maximum yield was achieved at a frequency of 40 kHz, extraction temperature of 60°C, F/S ratio of 0.01 g/mL, 25 minutes extraction time, and an airflow rate of 1 L/min. The resulting extracts were characterized using phytochemical screening, Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and gas chromatography (GC). Kinetic modeling, employing first- and second-order equations, demonstrated that the second-order kinetic model provided a better fit for both MAE and UAE processes, indicating complex interactions between solute and solvent. Overall, this study highlights the potential of MAE and UAE as efficient, eco-friendly alternatives for pigment extraction from Coleus leaves.